UNDERSTANDING THE IMPORTANCE OF THE PRINCIPLES OF COMMON LAW IN THE JUDICIAL DISCOURSE ACROSS THE COMMONWEALTH - Rodricks, Abhisekh (Commonwealth Law Review Journal, 2020)
The Commonwealth is one of the largest networks of countries which possess most customs in common, and the legal system followed in these countries is the Common Law system. The Common law system has proven to be one of the most efficient legal systems and probably the most followed as well across the world. Through this paper we have tried to understand the concept of Common law jurisprudence and its utilization within the judiciary as taught to the judicial officers at the time of judicial discourse. The understanding of the principles of Common law is of utmost importance keeping in mind the role of judges and the locus on hoe they apply the principles in order to tackle a case under the justice system. Hence the paper has actually compiled the foremost popular principles of law under the common-law system in order to better enhance the judicial system across the Commonwealth.